THE EFFECT OF BITTER MELON (Momordica charantia L.) JUICE AND BOILED EXTRACTON DIABETIC RATS - Fitri Electrika D. Surawan; Zulman Efendi (Jurnal Agroindustri, 2012)
Diabetes Mellitus (DM) is the most common of the endocrine disorder and chronic hyperglycaemia due to relative or absolute lack of insulin. The aim of the study is to investigate the the body weight profile, decreased of body weight (%) and glucose level of the bitter melon  juice and boiled extract dietin alloxan induced diabetic rats. Therats were divided randomly into three groups with fed AIN-93, the first group is control with water diet only, whereas the second group was given bitter melon juice extract diet, and third group with bitter melon boiled extract diet.  The diet of bitter melon juice and boiled extract were done by oral administration of 2ml/200 g body weight of rats for 8 days. The result showed that diet with bitter melon juice and boiled extract could improve body weight after 4 days. Additionally, the decreased of body weight percentage  afterbitter melon juice (2.68%) and boiled extract (1.89%) diet  were effective than control (8.81%). Bitter melon juice extract may effective in reduced  blood glucose levels than bitter melon boiled extract and control. The research indicate that bitter melon acts recovery body weight and regulating blood glucose level on diabetic rats.